Optical Control of Antimicrobial Activity in Quinolone Derivatives. Issue 32 (25th August 2017) - Contreras‐García, Elena; Martínez‐López, David; Alonso, Carla Andrea; Lozano, Carmen; Torres, Carmen; Rodríguez, Miguel A.; Campos, Pedro J.; Sampedro, Diego
Abstract : A series of photoswitchable compounds based on the antibiotics nalidixic acid and ciprofloxacin has been designed and prepared. Different photoactive moieties have been used as templates in order to allow for the photocontrol of the antimicrobial properties while providing the adequate photophysical features and solubility required for practical applications. The designed compounds feature strong absorptions up to the visible region, are water‐soluble and photoisomerize with high quantum yield. In the best case, a clear difference in the antimicrobial activity expressed as the minimal inhibitory concentration between the initial and the irradiated species was found. The complementary computational study allowed for the rationalization of the results found. Abstract : Different photoactive compounds based on the structures of nalidixic acid and ciprofloxacin, members of the large antibiotic family of quinolones, have been prepared. The reported compounds have been designed to modulate their activity by means of light. The photophysical properties and solubility are adequate for their use in biological applications.